HUKUM PERCERAIAN DISEBABKAN OLEH LIâAN - Faizin, Faizin (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2014)
According to Islamic law, the despair and the end of a marriage in a conjugal situation can occur at the instance of her husband through divorce. While the conclusion of a marriage is the will of the husband and wife can occur through curses, that the oath taken spouses in which there is the curse of God if the statement is not true with respect to his vow husband alleged that his wife had committed adultery with another man. The allegations in the absence of witnesses, as required for the issue of adultery four witnesses. My husband Saw his wife admitted having sexual relations with another person, whereas witness Saw the act of adultery, the wife or husband denies and says that for several months did not have sexual relations with a variety of reasons. Under the provisions of article 162 is a common thread that can be taken by the husband and wife do lian each other, then there was a break between them for ever. Children conceived following his mother.Menurut syariâat Islam, putus asa dan berakhirnya suatu perkahwinan dalam keadaan suami-istri dapat terjadi atas kehendak suami melalui talak. Sedangkan berakhirnya suatu perkawinan atas kehendak suami juga isteri dapat terjadi melalui liâan, yaitu sumpah yang dilakukan suami atau isteri yang didalamnya terdapat pernyataan sikap dilaknat Allah jika sumpahnya tidak benar sehubungan dengan tuduhan suami bahwa isterinya telah berbuat zina dengan laki-laki lain.Tuduhan itu tanpa kehadiran saksi, seperti disyaratkan untuk masalah perzinaan yaitu empat orang saksi. Suami mengaku menyaksikan isterinya melakukan hubungan seksual dengan orang lain, sebagailayaknya saksi menyaksikan perbuatan zina, atau suami mengingkari kandungan isterinya dan mengatakan bahwa selama sekian bulan tidak pernah melakukan hubungan seksual dengan berbagai alasan. Berdasarkan ketentuan pasal 162 tersebut dapat diambil benang merah bahwa suami-isteri saling melakukan liâan, maka terjadilah perpisahan antara keduanya untuk selama-lamanya.Â  Anak yang dikandung dimasabkan kepada ibunya